2017
DOI: 10.3389/fimmu.2017.01742
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Regulation of Innate Lymphoid Cell-Mediated Tissue Protection—Linking the Nutritional State to Barrier Immunity

Abstract: Innate lymphoid cells (ILC) are a recently described group of tissue-resident immune cells that play essential roles in maintaining and protecting the tissue barrier against invading pathogens. Extensive research has revealed that ILC-mediated immune responses are controlled by dietary components and metabolites. An additional role of ILC as important direct regulators of host metabolism and glucose tolerance is emerging. This suggests that ILC may act as key dietary sensors integrating nutritional and metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 76 publications
1
27
0
Order By: Relevance
“…Innate lymphoid cells (ILCs) are a recently discovered immune cell type, which plays an important role in lymphoid organogenesis, epithelial tissue homeostasis and defense, as well in the amplification of inflammatory responses [ 105 , 170 ]. Group 1 ILCs includes conventional Natural Killer (NK) cells and non-NK cell ILC1, which are characterized based on their ability to produce INF-γ and TNF-α in response to stimulation with IL-12, IL-15, or IL-18, and expression of the transcription factors T-bet and EOMES [ 172 ]. They play an important role in promoting responses against intracellular pathogens such as Toxoplasma gondii [ 173 ].…”
Section: The Effect Of Hypoxia On Innate Lymphoid Cell Function Anmentioning
confidence: 99%
See 2 more Smart Citations
“…Innate lymphoid cells (ILCs) are a recently discovered immune cell type, which plays an important role in lymphoid organogenesis, epithelial tissue homeostasis and defense, as well in the amplification of inflammatory responses [ 105 , 170 ]. Group 1 ILCs includes conventional Natural Killer (NK) cells and non-NK cell ILC1, which are characterized based on their ability to produce INF-γ and TNF-α in response to stimulation with IL-12, IL-15, or IL-18, and expression of the transcription factors T-bet and EOMES [ 172 ]. They play an important role in promoting responses against intracellular pathogens such as Toxoplasma gondii [ 173 ].…”
Section: The Effect Of Hypoxia On Innate Lymphoid Cell Function Anmentioning
confidence: 99%
“…In analogy to naïve human and murine T cells, resting NK cells predominantly use oxidative phosphorylation over aerobic glycolysis prior to activation [ 172 ]. Naïve NK cells possess limited requirements and they metabolize glucose through glycolysis coupled to oxidative phosphorylation to make ATP.…”
Section: The Effect Of Hypoxia On Innate Lymphoid Cell Function Anmentioning
confidence: 99%
See 1 more Smart Citation
“…Series of experiments showed that cholesterol synthesis pathway is essential for training of myeloid cells, which in turn are implicated in adiposeness and obesity . Furthermore, innate lymphoid cells (ILC) that are a group of tissue‐resident immune cells have been revealed to exert their vital functions through hosts dietary components and metabolites, which simultaneously affects host metabolism . In addition an intriguing view is presented by Paula Neto et al that food additives, which normally are considered harmless, can affect immune system cells that in turn modulates metabolic deregulations like obesity and diabetes.…”
Section: Immunometabolism In Metabolic Deregulationmentioning
confidence: 99%
“…9 Furthermore, innate lymphoid cells (ILC) that are a group of tissue-resident immune cells have been revealed to exert their vital functions through hosts dietary components and metabolites, which simultaneously affects host metabolism. 10 In addition an intriguing view is presented by Paula Neto et al 11 that food additives, which normally are considered harmless, can affect immune system cells that in turn modulates metabolic deregulations like obesity and diabetes. This notion is strengthened by the view that both immune disorders and abnormal metabolic states affect each other in bidirectional way, and more often than not immune activation leads to metabolically abnormal state which may be controlled by epigenetic mechanisms.…”
Section: Immunometabolism In Metabolic Dere Gulationmentioning
confidence: 99%